In situ metal-ion complexation and H2O2 oxidation for a pyridine-2, 6-dione based disperse yellow dye. (January 2017) - Peng, Yu-Xin; Zhao, Xiao-Lei; Xu, Dan; Qian, Hui-Fen; Huang, Wei
Abstract: We reported herein the studies on in situ metal-ion complexation and H2 O2 oxidation for a pyridine-2, 6-dione based heterocyclic dye (C.I. Disperse Yellow 211) in the hydrazone-tautomeric form. Our results reveal that four kinds of compounds can be isolated successfully by treating this dye with Cu(OAc)2 ·H2 O and H2 O2 in the presence of NH3 ·H2 O and DMF, namely oxidation and complexation product1, oxidation product2, ring-degradation (ring-opening and oxidative cleavage) product3 and complexation product4 . In contrast, when copper(II) and nickel(II) ions were used under the similar reaction condition just in the absence of H2 O2 oxidant, only direct complexation products4 and5 could be obtained. It is noted that organic compounds2 and3 adopt the same hydrazone-tautomeric form as that in C.I. Disperse Yellow 211, but all three dye-metal complexes1 and4 –5 exhibit the deprotonated azo form. A possible reaction mechanism is proposed for the formation of hydroxyl-addition and ring-degradation products1 –3 . Furthermore, we have provided an effective preparation method for new dyes with an additional ortho phenolic hydroxyl group by H2 O2 oxidation, metal-ion complexation and subsequent demetallization by Na2 S. Graphical abstract: We have studied herein in situ metal-ion complexation and H2 O2 oxidation for a pyridine-2, 6-dione based disperse yellow dye, where four kinds of compounds can be isolated successfully from the one-pot reaction including complexation, oxidation, oxidation and complexation, and ring-degradation products. Highlights: In situ Cu 2+ complexation and H2 O2 oxidation of a pyridine-2, 6-dione dye is described. Four products are isolated by treating this dye with Cu 2+ and H2 O2 in NH3 ·H2 O/DMF. A mechanism is proposed for hydroxyl-addition and ring-degradation products. A method for preparing new dyes with an additional o- Ph-OH group is proposed.